ANALISIS PENGARUH KEPEMIMPINAN YANG BERORIENTASI PERUBAHAN TERHADAP IKLIM KERJA DAN KINERJA KARYAWAN : KEPUASAN KERJA SEBAGAI VARIABEL MEDIATING PADA CV. SAC BERSAUDARA SAMARINDA - HENI AMELIA; SUKISNO S. RIADI; SAIDA ZAINUROSSALAMIA ZA (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
This study aims to determine the Influence Analysis Oriented Leadership Against Climate Change Labor and Employee Performance: Job Satisfaction As a mediating variable in the CV. SAC Brothers Samarinda. The independent variables in this study is oriented leadership and climate change Work while the dependent variable in this study is the Employee Performance. The population in this study were all employees of salesmen and sales supervisor at CV. SAC Brothers Samarinda. This type of research is the study population invitation purposive sampling techniques or methods with quantitative approach. The data collection is done by using a survey method through the distribution of questionnaires to the respondents. The analytical tool used in this research is using Partial Least Square (PLS). Hypothesis testing results indicate that the constructs of leadership is not significant positive effect on job satisfaction directly construct. Leadership is not significant positive effect on employee performance constructs directly. Working climate construct significant positive effect on employee satisfaction directly. The climate of significant positive effect on employee performance constructs directly. Job satisfaction is not significant positive effect on employee performance constructs directly.Keyword: Oriented Leadership, Climate Change Work